2012
DOI: 10.1007/s00508-012-0237-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasites of rodents from the Chittagong Hill Tracts in Southeastern Bangladesh

Abstract: Rodents are a key mammalian group highly successful in adapting to a variety of environments throughout the world and play an important role in many zoonotic cycles. Within this project, the gastrointestinal and extraintestinal parasite fauna of 76 rodents (Muroidea and Sciuridae) was determined in the District of Bandarban (Chittagong Hill Tracts) in Southeastern Bangladesh. Gastrointestinal and extraintestinal parasites were examined with macro- and microscopical tools (e.g. Ziehl-Neelsen Staining) at a fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…( R. norvegicus and/or R. rattus )100 % (of 12)PhilippinesClaveira et al (2005)34 %Japan (Southern Anami Islands)Kamiya et al (1968)44 % (of 82)FranceDavoust et al (1997) Rattus spp. ( Rattus rattus diardii , R. norvegicus , and R. exulans )21.6 %MalaysiaParamasvaran et al (2009) Rattus sp.11.9 %France—Lyon ZooApéry (2012)13 %France—Vincennes ZooApéry (2012) Rattus rattus sladerni 38.8 %China (Yunnan Province)Shen et al (2003)33 % (1/3)China (Yunnan Province)Xiong et al (1999)Polynesian rat ( Rattus exulans )New ZealandRoberts (1990)IndonesiaBrown et al (1975b)MalaysiaLiat et al (1977); Sinniah et al (1979)37.5 %MalaysiaSyad-Arnez and Mohd Zain (2006)Sikkim rat ( Rattus andamanensis )8.3 % (1/12)BangladeshFuehrer et al (2012)Rice-field rat ( Rattus argentiventer )IndonesiaBrown et al (1975b)MalaysiaMulkit and Cheong (1971); Liat et al (1977); Sinniah et al (1979)Lesser rice-field rat ( Rattus losea )5.4 %TaiwanYang and Lu (2000)38.9 %China (Fujian Province)Yuan et al (2000)Hoffmann's rat ( Rattus hoffmanni )IndonesiaBrown et al (1975b)Opossum rat ( Rattus marmosurus )IndonesiaBrown et al (1975b)<...>…”
Section: Muroidea Host Spectrummentioning
confidence: 99%
“…( R. norvegicus and/or R. rattus )100 % (of 12)PhilippinesClaveira et al (2005)34 %Japan (Southern Anami Islands)Kamiya et al (1968)44 % (of 82)FranceDavoust et al (1997) Rattus spp. ( Rattus rattus diardii , R. norvegicus , and R. exulans )21.6 %MalaysiaParamasvaran et al (2009) Rattus sp.11.9 %France—Lyon ZooApéry (2012)13 %France—Vincennes ZooApéry (2012) Rattus rattus sladerni 38.8 %China (Yunnan Province)Shen et al (2003)33 % (1/3)China (Yunnan Province)Xiong et al (1999)Polynesian rat ( Rattus exulans )New ZealandRoberts (1990)IndonesiaBrown et al (1975b)MalaysiaLiat et al (1977); Sinniah et al (1979)37.5 %MalaysiaSyad-Arnez and Mohd Zain (2006)Sikkim rat ( Rattus andamanensis )8.3 % (1/12)BangladeshFuehrer et al (2012)Rice-field rat ( Rattus argentiventer )IndonesiaBrown et al (1975b)MalaysiaMulkit and Cheong (1971); Liat et al (1977); Sinniah et al (1979)Lesser rice-field rat ( Rattus losea )5.4 %TaiwanYang and Lu (2000)38.9 %China (Fujian Province)Yuan et al (2000)Hoffmann's rat ( Rattus hoffmanni )IndonesiaBrown et al (1975b)Opossum rat ( Rattus marmosurus )IndonesiaBrown et al (1975b)<...>…”
Section: Muroidea Host Spectrummentioning
confidence: 99%
“…Studies identified Rattus rattus , Rattus norvegicus , Mus musculus , Dasyprocta , and Hydrochoerus hydrochaeris as carriers of Strongyloides spp. [16,17,18,19,20,21,22]. Sample sizes for rodent-based studies ranged from 10 to 502.…”
Section: Resultsmentioning
confidence: 99%
“…Quanto aos helmintos de roedores, os cestódeos do gênero Hymenolepis são frequentemente observados parasitando estes animais (GALAN-PUCHADES, 2015). E são listados entre os enteroparasitos de grande importância em saúde pública de humanos…”
Section: Parasitos Gastrointestinais De Roedoresunclassified